The semantic roles of ‘kaku-joshi’ in Japanese textbooks - Sutedi, Dedi (Indonesian Journal of Applied Linguistics, 2020)
Case particles are an important Japanese language learning aspect that the learners should have learned since the beginner level, yet there are still many who still do not grasp the meaning and function of each particle. This is because in the instructional process, the elaboration of such articles is confined to the external structure, while the inner structure (semantic roles) is rather neglected in the textbooks. This study seeks to explain each semantic role of the particles 'kaku-joshi' contained in Japanese language teaching materials starting from elementary to secondary levels used in Indonesia. The method used is descriptive, with textual analysis employed as a data analysis technique. Findings reveal that all Japanese case particles have appeared in elementary level textbooks, namely particles GA, WO, NI, DE, TO, E, KARA, MADE, and YORI which are used to follow arguments or syntactic functions in the form of subject, object, complement, and adjunct. However, not all semantic roles appear in the textbook; 14 semantic roles are evidently not present. The findings of this study can be used as reference material for Japanese instructors in the teaching of Japanese case particles, so that the differences among the particles will be clearer and more easily understood by Japanese language learners in Indonesia.